Photon upconversion heterostructures made from surface-anchored metal-organic frameworks - Oldenburg, Michael (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2019)
This work deals with the process of photon upconversion in surface-anchored metal-organic frameworks. During the upconversion, two low-energy photons are absorbed and fused into a higher-energy photon, which is emitted. In this work, this process is analyzed in surface-bound metal-organic frameworks by spectroscopic methods. Furthermore, the application for increasing the efficiency of solar cells is discussed.